Exotic species dominate marinas between the two most populated regions in the southwestern Atlantic Ocean - Oricchio, Felipe T.; Marques, Antonio C.; Hajdu, Eduardo; Pitombo, Fabio B.; Azevedo, Fernanda; Passos, Flávio D.; Vieira, Leandro M.; Stampar, Sergio N. [UNESP]; Rocha, Rosana M.; Dias, Gustavo M. (Elsevier, 2019)
Human occupation of coastal areas promotes the establishment of non-native species but information on bioinvasions is usually biased toward the Northern Hemisphere. We assessed non-native species' importance in sessile communities at six marinas along the most urbanized area of the Southwestern Atlantic coastline. We found 67 species, of which 19 are exotic. The most frequent species was the exotic polychaete Branchiomma luctuosum, while the most abundant was the exotic bryozoan Schizoporella errata that monopolized the substrata in three marinas. Along with S. errata, the exotic polychaete Hydroides elegans and ascidian Styela plicata dominated space in the three remaining marinas, while native species were in general rare. We show that communities associated with artificial substrata along this Brazilian urbanized area are dominated by exotic species and that using abundance data along with species identity can improve our understanding of the importance of exotic species for the dynamics of biological communities.
Keywords: Anthropogenic impact; Benthic species; Community homogenization; Non-indigenous species; Schizoporella errata